Pengembangan Sistem Informasi Pengaduan Eksploitasi Anak Berbasis Android - Farid Farid; Siti Andini Utiarahman; Moh. Fachrinanda Putra Bowta (JURIKOM (Jurnal Riset Komputer), 2022)
Children have the right to live, grow and develop and receive protection from violence and discrimination. Exploitation is a complex and modern type of violence against humanity. In the city of Gorontalo there is still a lot of exploitation of children. The Gorontalo city government provides services to the community to be able to report violence and exploitation that occurs in their environment with a web-based complaint information system. The website-based complaint information system is still considered less flexible, because some websites are less responsive. In addition, the complaint website created by the Gorontalo city government is not optimal because it does not have a location tracking feature to find out the location of the complainant. The author aims to develop an Android-based child exploitation complaint information system to be used by the public to report acts of child exploitation to speed up the investigation of reports reported by the public anywhere, anytime and add a tracking location menu to find out the location of the complainant and the feature to send pictures or videos as evidence of the report. complaint. The research uses research and development methods. The results of testing the test case system obtained that the registration module obtained a value of V(G) = 2 and Cyclometic Complexity (CC) = 2, the authors concluded that the logic flow in the registration module in the system designed to run effectively